Development a new costing structure for palm oil industry using time driven activity based costing - Mohd Yazid, Abu; S.N.A.M., Zaini (IOP Publishing, 2020)
Palm oil is one of the agricultural commodities most marketable in the world. The Malaysian palm oil industry is undoubtedly the pride of the country. There are few problems in this plantation at present, which do not represent a time frame to measure operations deviation, a rate establishment did not properly explain the connection between supplied assets and functional capacity and a method for tracking unused capacity was not available to the manager. This work aims at developing a new costing model specifically for ramp areas for improved precision. Time-driven activity-based costing (TDABC) is introduced because it can measure time output effectively, correctly identify idle energy and separately list the unused capacity. Costing based on time activity has been implemented. It also offers a better understanding of operating instruments and associated costs when assessing processes and promoting improvements in quality. There are three main divisions in the plantation in Pahang. The maximum utilized ramp capacity and the level of capacity cost rate (CCR) were successfully established with 4800 minutes and 1.00 RM / minute respectively. Finally, the manager finds the unused capability that can be used to improve ramp-resource management on a regular basis. However, the unused capacity created in ramp activities is not present in this case study.